Early combination of sotrovimab with nirmatrelvir/ritonavir or remdesivir is associated with low rate of persisting SARS CoV-2 infection in immunocompromised outpatients with mild-to-moderate COVID-19: a prospective single-centre study - I. Gentile; G. Viceconte; F. Cuccurullo; D. Pietroluongo; A. D’Agostino; M. Silvitelli; S. Mercinelli; R. Scotto; F. Grimaldi; S. Palmieri; A. Gravetti; F. Trastulli; et al. (Annals of Medicine)
Background Immunocompromised patients are at high risk of developing persisting/prolonged COVID-19. Data on the early combined use of antivirals and monoclonal antibodies in this population are scarce.Research design and methods We performed an observational, prospective study, enrolling immunocompromised outpatients with mild-to-moderate COVID-19, treated with a combination of sotrovimab plus one antiviral (remdesivir or nirmatrelvir/ritonavir) within 7 days from symptom onset. Primary outcome was hospitalization within 30 days. Secondary outcomes were: needing for oxygen therapy; development of persistent infection; death within 60 days and reinfection or relapse within 90 days.Results We enrolled 52 patients. No patient was hospitalized within 30 days of disease onset, required oxygen administration, died within 60 days, or experienced a reinfection or clinical relapse within 90 days.The clearance rates were 67% and 97% on the 14th day after the end of therapy and at the end of the follow-up period, respectively.Factors associated with longer infection were initiation of therapy 3 days after symptom onset and enrollment for more than 180 days from the beginning of the study. However, only the latter factor was independently associated with a longer SARS-CoV-2 infection, suggesting a loss of efficacy of this strategy with the evolution of SARS-CoV-2 variants.Conclusions Early administration of combination therapy with a direct antiviral and sotrovimab seems to be effective in preventing hospitalization, progression to severe COVID-19, and development of prolonged/persisting SARS-CoV-2 infection in immunocompromised patients.